PERLINDUNGAN HUKUM BAGI PEKERJA KONTRAK APABILA DI PHK PADA MASA KONTRAK BERLANGSUNG - Muhamad Dela Dwi Mustofa; Hufron Hufron (Gapenas Publisher, 2022)
Legal protection relates to government power and economic power. With regard to the people, in Article 1 paragraph 3 of Law Number 13 of 2003 concerning employment, a worker or laborer is anyone who works by receiving wages in other forms. The work agreement is divided into two, namely the Specific Time Work Agreement and the Indefinite Work Agreement. Definition of Contract Workers are those who work based on a certain time work agreement (PKWT), namely a work agreement between the entrepreneur and the worker to hold a working relationship for a certain time or for a certain job. If in the employment agreement the entrepreneur terminates the employment relationship (PHK), namely the termination of the employment relationship due to a certain matter that results in the termination of the rights and obligations of the worker, it is very important to provide legal protection to the worker/laborer. The author here will discuss the problem of regulating the normative rights of workers / laborers who are laid off during the contract period according to Law no. 11 of 2021 concerning Job Creation and how is the legal protection for workers/ labourers who have been laid off during the contract period. The purpose of the author is of course to find out the normative rights arrangements of workers who have been laid off during the contract period and to find out what legal protections are obtained by these workers / laborers. This type of research has used the type of research from normative law. The result of the writing that the author discusses is that the party who ends the employment relationship is required to pay compensation to the other party in the amount of the worker's salary until the expiration of the work agreement period